Role of Magnesium Sulphate in Postoperative Analgesia - Archana Agarwal; Neeraj (Academia Anesthesiologica International, 2019)
Background: The present study was conducted to evaluate role of magnesium sulphate on postoperative pain relief. Subjects and Methods: The present study was conducted on 76 patients of ASA grade I and II for surgery. Patients were divided into 2 groups of 38 each. Group I patients were given magnesium sulphate (50mg/kg,i.v.) and group II was control. Pain at rest was evaluated using a 0-10 cm VAS at emergence from anaesthesia and 2, 4, 8, 16 and 24 hrs after surgery. Results: The VAS score at emergence from anaesthesia was 1.82 in group I and 1.94 in group II, after 2 hours VAS was 1.35 in group I and 1.54 in group II, after 4 hours was 1.42 in group I and 1.89 in group II, after 8 hours was 2.68 in group I and 3.12 in group II, after 16 hours was 1.32 in group I and 2.01 in group II and after 24 hours was 0.71 in group I and 1.21 in group II. The difference was significant (P< 0.05). The mean sedation score in group I was 1.82 and in group II was 1.43. The difference was significant (P< 0.05). Conclusion: Authors found that administration of intravenous magnesium sulphate preoperatively significantly reduces postoperative pain in patients.